PERFORMANCE INVESTIGATION OF SOLAR WATER HEATER INTEGRATED WITH PCM AND PCM NANOCOMPOSITE THERMAL ENERGY STORAGE - SAW, CHUN LIN (2013)
A solar water heater is part of a solar thermal system which is mainly used for domestic water heating applications. The system performance is influenced by many designs and operating parameters and its functionality is governed by the solar radiation availability. The aim of this research has been to investigate the performance enhancement of the solar water heater by integration with thermal energy storage (TES). This may eliminate the dependency on an electric heater during the unavailability of solar radiation. An experimental investigation and an analytical assessment were carried out The analytical assessment involved the use of fluid flow and thermal field equations to generate a mathematical model of a newly developed solar-PCM-TES integrated system. The mathematical model was programmed and solved in a MATLAB software environment